Effect of Water on HEMA Conversion by FT-IR Spectroscopy - TS. Jafarzadeh Kashi; M. Erfan; DC. Watts (Tehran University of Medical Sciences, 2007)
Objective: The use of HEMA as a biocompatible material in dentin bonding systems and its potential for clinical applications has been well established. Excess water can affect conversion of bonding resins. The aim of this study was to survey the effect of water on the degree of conversion of HEMA by Fourier Transform Infra-red Spectroscopy (FT-IR). Materials and Methods: In this experimental study, distilled water was added in amounts of 0, 0.05, 0.1, 0.2, and 0.4 ml to 1 ml of curable HEMA solution. Six repetitions per water ratio were made and investigated. Each sample was polymerized for 60 seconds. Degree of conversion was obtained from the absorbance IR-Spectrum of the materials before and after polymerization by FT-IR spectroscopy. One way ANOVA and Tukey-HSD were carried out to compare and detect any differences among groups. Results: Statistical analysis indicates highly significant difference between pairs of groups at level (P<0.001). The results showed a trend of decreasing in HEMA conversion with increasing water. Degree of conversion changes significantly within the 0.05 ml to 0.2 ml water range. However, degree of conversion did not change after reaching 0.02 ml and before 0.05. Conclusion: Degree of conversion of HEMA decreased by increasing water. The most dramatic effect of water on the polymerization process occurs within a range which exists under clinical conditions. The reason that the degree of conversion did not show significant result before 0.05 ml may be related to the hydrophilic nature of HEMA.